Huggable Communication Medium Maintains Level of Trust during Conversation Game - Takahashi, Hideyuki; Ban, Midori; Osawa, Hirotaka; Nakanishi, Junya; Sumioka, Hidenobu; Ishiguro, Hiroshi (Frontiers in Psychology, 2017)
There have been several attempts in recent years to develop a remote communication device using sensory modalities other than speech that would induce a user’s positive experience with his/her conversation partner. Specifically, Hugvie is a human-shaped pillow as well as a remote communication device enabling users to combine a hugging experience with telecommunication to improve the quality of remote communication. The present research is based on the hypothesis that using Hugvie maintains users’ level of trust toward their conversation partners in situations prone to suspicion. The level of trust felt toward other remote game players was compared between participants using Hugvie and those using a basic communication device while playing a modified version of Werewolf, a conversation-based game, designed to evaluate trust. Although there are always winners and losers in the regular version of Werewolf, the rules were modified to generate a possible scenario in which no enemy was present among the players and all players would win if they trusted each other. We examined the effect of using Hugvie while playing Werewolf on players’ level of trust toward each other and our results demonstrated that in those using Hugvie, the level of trust toward other players was maintained.